The Design of Cognitive Training Games for the Thai Elderly - Tantisatirapong, Suchada; Puttapirat, Pargorn; Senavongse, Wongwit; Chanwimalueang, Theerasak (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2021)
Cognitive aging is one of the main public health concerns, often involving a decline in memory and decision-making abilities as people age. Cognitive training games have been widely employed to improve working memory as well as enhancing short and long-term memory. In this study, we aim to develop a cognitive training game based on speech recognition technology under a Thai setting based user interface. The designed cognitive training tasks were conducted by performing electroencephalography (EEG) on six elderly volunteers, who passed the Thai mental state examination. The participants were instructed to memorize a series of pictures and calculate simple math questions. The EEG signals of the participants were recorded and analyzed during training. The participants engaged in four cognitive training tasks with three trials. An increase in training scores was found to be related to a rise in three EEG power spectrum bands: theta, alpha, and beta. Participants expressed the highest average level of satisfaction towards the easiest tasks in the four cognitive training games. This implies that when performing an easy task, an increase in the power spectral density of three EEG bands tends to evidently occur. As a result, the proposed cognitive training game could leverage the working memory of the Thai elderly. The game design can be enhanced by integrating human-based interactive tasks, such as handwriting and eye movements. Its replication on a larger scale should be assessed in the future work.